Visibility of car door vibrations during closure - Lemasle, Guillaume (My University, 2004)
This work is intended to apprehend which door vibrations contribute to the visible motion occuring during closure,where they emanate from and how they may be abolished. The human ability to distinguish mechanical vibrations is not well-known and should be experimentally investigated. On account on its inertia, the eye perception weakens over frequency and, in particular, no dynamic motion can be discerned over 50 Hz. This determines the upper frequency limit of visibility and rejects the currently assumed value 10 Hz higher. Below 50 Hz, mechanical vibrations may be visible as long as their amplitude is larger than an experimentally-defined threshold. The frequency domain of interests is deep. During the closure process, the main excitation arises from the water strips that brake the door and transmit energy into inner panels. The resulting vibrations travel towards outer panels because of the strong coupling between the both. Provided that the door natural properties that are likely to be excited from the closure process do not appear below 50 Hz, no external vibrations will be distinguished.Inner panels act as transfer systems between excitation and outer panels, thus their construction must be specifically emphasised. As a rule the current structures are not stiff enough,in particular inner door panels that turn out to be a source of weakness. Practical ways to improve the construction are discussed and must be further investigated, for instance using FEM calculations, of which consistence is assessed in this work.
Keywords: Samhällsbyggnadsteknik; Civil Engineering